2020
DOI: 10.1111/bcp.14574
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasmodium vivax malaria and antimalarial treatment on cytochrome P450 activity in Brazilian patients

Abstract: Aims: To investigate the impact of Plasmodium vivax malaria and chloroquineprimaquine chemotherapy on CYP2D6 and CYP2C19 activity in patients from the Brazilian Amazon. Methods: Adult patients (n = 30) were given subtherapeutic doses of CYP2D6 and CYP2C19 phenotypic probes metoprolol (10 mg) and omeprazole (2 mg) in three different stages of vivax malaria illness: acute disease (study phase 1), post chemotherapy (phase 2) and convalescence (stage 3). Plasma concentrations of probes and CYP-hydroxylated metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(87 reference statements)
2
8
0
Order By: Relevance
“…The data also show that CYP2C19 metabolic activity does not differ between patients with mild to moderate hepatic fibrosis (fibrosis stages F0/F1 and F2) and patients with advanced liver fibrosis (F3 and F4) after treatment with DAAs for HCV. In addition to HCV infection, other studies from our research group have also demonstrated that CYP2C19 inhibition was at least partially reversed after treatment for other infectious diseases with a key inflammatory component, such as visceral leishmaniasis and malaria 9,10 . Through the lens of translational pharmacology, the present study reinforces that the administration of drugs which are substrates for CYP2C19 (amitriptyline, clomipramine, clopidogrel, hexobarbital, imipramine, lansoprazole, melatonin, nelfinavir, omeprazole, pantoprazole, progesterone, proguanil, R‐mephobarbital, ranitidine, S‐mephenytoin, venlafaxine, voriconazole) 42 before or during the treatment with DAAs for HCV should take into account the dosing regimen, once the activity of this CYP isoform is inhibited, similar to what has been shown in the past for parasitic infections.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The data also show that CYP2C19 metabolic activity does not differ between patients with mild to moderate hepatic fibrosis (fibrosis stages F0/F1 and F2) and patients with advanced liver fibrosis (F3 and F4) after treatment with DAAs for HCV. In addition to HCV infection, other studies from our research group have also demonstrated that CYP2C19 inhibition was at least partially reversed after treatment for other infectious diseases with a key inflammatory component, such as visceral leishmaniasis and malaria 9,10 . Through the lens of translational pharmacology, the present study reinforces that the administration of drugs which are substrates for CYP2C19 (amitriptyline, clomipramine, clopidogrel, hexobarbital, imipramine, lansoprazole, melatonin, nelfinavir, omeprazole, pantoprazole, progesterone, proguanil, R‐mephobarbital, ranitidine, S‐mephenytoin, venlafaxine, voriconazole) 42 before or during the treatment with DAAs for HCV should take into account the dosing regimen, once the activity of this CYP isoform is inhibited, similar to what has been shown in the past for parasitic infections.…”
Section: Discussionsupporting
confidence: 81%
“…In vitro , 7 in silico 6,8 and clinical 9,10 studies demonstrate that high plasma concentrations of IL‐6 suppress the expression and, consequently, the activity of multiple CYP isoforms. Plasma concentrations of interleukin 6 (IL‐6) in healthy volunteers range from 1 to 10 pg mL −1 , but may increase to 10‐1500 pg mL −1 in patients with inflammatory diseases, such as rheumatoid arthritis 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CQ can partially inhibit CYP2D6 activity, as evaluated by the phenotypic probes debrisoquine ( Adedoyin et al, 1998 ) and metoprolol ( Lancaster et al, 1990 ; Almeida et al, 2020 ), thereby decreasing the generation of pharmacologically active PQ metabolites. A decrease in CYP2D6-mediated biotransformation might explain the increased plasma levels of PQ and cPQ measured in healthy individuals co-administered CQ and PQ, compared with those given PQ alone ( Pukrittayakamee et al, 2014 ).…”
Section: Therapeutic Efficacy Trials Of Hypnozoitocidesmentioning
confidence: 99%
“…(see above). However, it should be emphasized that in both studies, the cohort of decreased CYP2D6 activity (AS ≤ 1) included none 23 or few (< 6%) 14 poor metabolizers (AS = 0) and consequently the apparent lack of association between decreased CYP2D6 activity and anti‐relapse efficacy of tafenoquine may not be extrapolated to poor metabolizers. This is especially relevant in view of the evidence from murine malaria models that the anti‐relapse effect of tafenoquine is abolished by CYP2D knock‐out, which may be seen as equivalent to the human CYP2D6 poor metabolizer phenotype (AS = 0), rather than intermediate metabolizer phenotypes.…”
Section: Human Studiesmentioning
confidence: 99%
“…We have recently verified the inhibitory effect of chloroquine on CYP2D6‐mediated hydroxylation in patients with P . vivax and discussed this finding in the context of apparent discrepancy between the well‐demonstrated enhancement of primaquine anti‐malarial efficacy by chloroquine and the notion that CYP2D6 activity is essential to the anti‐malarial efficacy of primaquine 23 …”
Section: Human Studiesmentioning
confidence: 99%